Tretinoin or retinol enhancement of lymphokine-activated killer cell proliferation and cytotoxicity against human bladder cancer cells in vitro - Wang Zhi-Ping; Zheng Rong-Liang; Chen Yi-Rong; Liu Guo-Dong (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of tretinoin (Tre) or retinol (Ret) on the proliferation of lymphokine-activated killer (LAK) cells in patients with transitional cell cancer of bladder and their cytolysis to bladder tumor cells. METHODS: LAK cell proliferation was assayed in the presence of either Tre or Ret by cell counting. Human transitional bladder cancer cell lines BIU-87, EJ, or bladder tumor cells (BTC) from patients with bladder cancer were used as target cells and cytotoxicity of LAK cells was determined by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. RESULTS: The proliferation of LAK cells induced by interleukin-2 (IL-2) was stimulated by Tre or Ret (10-100 nmol.L-1). The cytotoxicity of LAK cells against BIU-87, EJ cells, or BTC was enhanced by pretreatment of LAK cells with Tre or Ret 10-100 nmol.L-1. CONCLUSION: Tre or Ret enhances the proliferation and cytotoxicity of LAK cells from patients with bladder cancer. Retinoids are potential in adoptive immunotherapy of bladder cancer.